EFFECTS OF EXPATRIATES' COMMITMENT ON MULTINATIONAL CORPORATIONS' INTERNATIONAL ASSIGNMENT - Kurbonova Dildora Murotovna (American Journals, 2023)
This article examines the role of expatriates and workers and to determine the influence of the three-component conceptualization of organizational commitment towards companies along with their environmental reputation in their foreign assignments. The study used a methodological approach in which the questionnaire survey was used to gather quantitative data and other observational methods and concluded that there are several variables in the assessment of employee commitment, and the findings reinforce the significance of those mentioned below for organizational commitment in international contexts. The implications for commitment analysis and the importance of environmental reputation are explored.
Keywords: expatriates, three component conceptualization, employee commitment, organizational commitment, quantitative data.